Extended spectrum beta-lactamase producing Escherichia coli in pet cats and dogs in Central Peninsular Malaysia - Dzulkifli, Khaleeda Azalea; Hassan, Latiffah; Zakaria, Zunita; Megat Abdul Rani, Puteri Azaziah; Ahmad, Nur Indah (John Wiley and Sons Inc, 2025)
Background: Epidemiological study of pets in Malaysia as reservoirs for antimicrobial resistant bacteria is unknown. Objectives: This study aims to determine the extended-spectrum beta-lactamase (ESBL) producing Escherichia coli from rectal swabs pet cats and dogs in the central region of Peninsular Malaysia. Materials and Methods: A cross-sectional study on physically healthy pet cats and dogs was conducted in the Klang Valley between 2019 and 2020. Rectal swabs were collected for ESBL-producing E. coli identification and detection. A questionnaire was used to collect pet data, and univariable and multivariable analysis was conducted to determine risk factors ESBL-producing E. coli detection. Results: A total of 160 rectal swabs were collected from physically healthy pets in the Klang Valley, with 6.8% (n = 11) dogs and 3.8% (n = 6) cats were positive for ESBL-producing E. coli (10.6%). The highest resistance demonstrated by the ESBL isolates was towards ampicillin, cephalexin and cefotaxime (100%). Multiple-drug resistance of the ESBL-isolates was high, with 91.7% (n = 22) and 68.8% (n = 11) in dogs and cats. The most predominant ESBL genes was blaCTX-M (43.2%). None of these isolates carried blaSHV. Dogs were four times more likely to carry ESBL-producing E. coli in their faeces compared to cats. ESBL-producing E. coli carriage was positively associated in dogs, among pets sharing feeding area or pets with a history of gastrointestinal symptoms. Conclusion: ESBL-producing E. coli in cats and dogs in Malaysia was determined at 10.6%, with dogs at a greater risk of carrying the bacteria. Co-resistance to more than three types of tested antibiotics for the ESBL-producing E. coli isolated was high. Pets act as reservoirs for antimicrobial resistance (AMR) and resistance genes that can be shared with human through interactions. Antimicrobial stewardship remains critical to safeguard not only antibiotics but also the health of pets and humans.